The High School English Teacher's Experience in Actualizing Howard Gardner's Multiple Intelligence Theory in Teaching - Kurnia Annisa; Kisman Salija; Maemuna Muhayyang (Journal of Excellence in English Language Education, 2023)
This research aimed to find out the strategy used by the English teacher in actualizing multiple intelligence in teaching and the ways of the English teacher uses the strategy in actualizing multiple intelligence in teaching. This research applied the descriptive qualitative method. The data was collected from interviews using Zoom meetings and documentation of the English teacher’s lesson plans. The data was taken from the teacher at Bosowa School Makassar. The result of this research showed that the English teacher at Bosowa School Makassar applied almost all of the multiple intelligence in his teaching strategies, excluding musical intelligence. These strategies are (1) linguistic intelligence; regulation to speak English, debate, and write a personal letter, (2) logical-mathematical intelligence; English riddle games, (3) spatial intelligence; caption material and hot seating game, (4) bodily-kinesthetic intelligence; treasure hunting game, (5) interpersonal intelligence; make dialog, (6) intrapersonal intelligence; daily journal, and (7) naturalist intelligence; field trip. The English teacher distinguished the way he used strategy in actualizing multiple intelligence to encourage and motivate students to enhance their skills in learning.  It can be concluded that using various strategies in actualizing multiple intelligence in teaching can encourage and motivate students to enhance their skills in learning.